Doença respiratória em bezerros – relato de caso - Silva, Raphael Oliveira de Sá e (Universidade Federal do Tocantins, 2022)
This report aims to describe the routine and activities performed in the mandatory curricular internship of Veterinary Medicine course of Federal University of Tocantins. The internship was conducted from September 11th to November 17th 2021, with a workload of 345 hours, in the areas of clinical, surgery and reproduction of large animals; it was also possible to follow activities related to technical assistance to rural properties, as well as registration of Senepol cattle. This report describes a clinical case of respiratory disease in a calf, elucidating the impact of the disease on herd health and animal welfare.